A mudança da postura estratégica da Turquia na Guerra Civil da Síria: explicando o uso da força a partir de dinâmicas domésticas e estruturais - Santos, Vlademir Monteiro do (2020)
This dissertation intends to analyze the change in Turkey's strategic behavior in the Syrian Civil War. Between 2016 and 2018, its Armed Forces carried out two military offensives in that country, with the aim of containing threats to national security, produced in the context of this conflict. However, such conduct contrasts with the approach adopted so far. Although it has considered, on other occasions, to undertake incursions into Syrian terrain, Ankara preferred a less risky exhibition that focused on the use of proxy war. Against this background, this research is based on the premise that Turkey's use of force represents a break with its strategic stance. Therefore, the main aim is to explain this inflection based on a theoretical framework that mixes the models of Rational Choice and Government Policy, developed by Allison and Zelikow, with neoclassical realism. In the methodological aspect, the work employs a qualitative approach and is structured as oriented case study.